In utero undernourishment during WWII: Effects on height and weight of young adult women - Czapla, Zbigniew; Liczbińska, Grażyna; Piontek, Janusz; Malina, Robert M. (Anthropological Review, 2020)
Under marginal nutritional conditions, growth in utero is related to subsequent growth and adult height. The aim of this research is to compare the young adult body size of women grouped by estimated duration of pregnancy relative to World War II. Subjects were 620 university students 18-25 years, for whom archival data for date of birth, age, height and weight were available; the BMI was calculated. Based on estimated time of pregnancy and birth relative to WWII, the women were grouped as follows: (1) pregnancy and birth before the war (n=203); (2) pregnancy before the war, birth during the war (n=54); (3) pregnancy and birth during the war (n=173); (4) pregnancy during the war, birth after the war (n=16); and (5) pregnancy and birth after the war (n=174). Heights of women born before and after WWII were significantly taller than heights of women born during the war. Though not significant, the height of women who were conceived before but born during the war was intermediate between those of women born before and during the war. The height of women conceived during the war but born after the war was similar to that of women conceived and born during the war. In contrast, BMIs and the distributions of women by weight status did not differ among the five pregnancy groups. The results suggested that heights of young adult women exposed in utero to the conditions of WWII (marginal nutritional status, maternal stress, among other factors) were shorter than women who were not exposed in utero to wartime conditions.